Konkurencja w gastronomii zamkniętej na przykładzie wybranych szkół podregionu wrocławskiego i Wrocławia - Kowalska, Anna (Competition in School Gastronomy on the Example of Chosen School in Wroclaw Subregion and in Wroclaw City, 2006)
Private firms are getting more interested in offering their services to schools. A choice of a firm offering gastronomic services is led by following reasons: prices offered for a meal, quality of services and also additional benefits which a private firm may offer the school. Schools in big cities are the ones that use the services of private gastronomic services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 469-476